Relation between length of stay and anti-filarial igg4 level in pondok gede sub-district, bekasi district, west java - Susatyo, Jeffry Adijaya; Wibowo, Heri (Folia Medica Indonesiana, 2017)
Filariasis is a contagious disease caused by worms of the genus Filaria which transmitted through the bite of various species of mosquitoes. In Indonesia, the existence of filariasis cases are still very concerning. Jati Sampurna and Jati Karya villages in Pondokgede Sub-district, Bekasi District, West Java have been known as filariasis endemic area. Length of stay is presumed as one of many factors that affects filariasis occurrence in those villages. This study aimed to determine the distribution of anti-filarial IgG4 on the region and its comparison with the length of stay and residence status. This study was based on secondary data. Secondary data were obtained from primary research data done by cross-sectional method. These data were used to assess the correlation of filarial infection risk factors in pregnant women living in endemic areas based on the distribution of anti-filarial IgG4 in Pondok Gede, Bekasi district, West Java. The study showed that there was an increase in anti-filarial IgG4 against residence status (p=0.017) and a positive correlation between the number of anti-filarial IgG4 with length of stay in years (p=0.003).